Why and how do microbubbles enhance the effectiveness of diagnostic and therapeutic interventions in cerebrovascular disease? - Meairs, Stephen; Kern, Rolf; Alonso, Angelika (Current pharmaceutical design, 2012)
Rapid advances in microbubble pharmacology together with novel ultrasound technologies for contrast-specific imaging of the macro- and microcirculation have led to a number of new applications for assessment of stroke patients. In particular, ultrasound perfusion imaging has added new perspectives for diagnosis and monitoring of both ischemic and hemorrhagic stroke. Recently, real-time brain perfusion imaging of middle cerebral artery infarctions has been introduced and new quantitative algorithms for evaluation of regional cerebral blood flow are being applied for the first time in humans. Microbubbles enable visualization of carotid artery plaque neovascularization to detect plaque vulnerability. There is growing interest in therapeutic applications of ultrasound, particularly in the field of sonothrombolysis. The treatment of acute ischemic stroke can be improved by ultrasound and microbubbles in combination with thrombolytic drugs. Excitingly, ultrasound and microbubbles may be effective in clot lysis of ischemic stroke even without additional thrombolytic drugs. New therapeutic avenues include opening of the blood-brain barrier (BBB) with ultrasound and microbubbles to enable novel drug delivery to the brain. Microbubbles are also assuming a central role in ultrasound molecular imaging with many targets of interest for evaluating pathophysiologic processes involved in cerebrovascular disease including angiogenesis, inflammation, and thrombus formation.